The Association of Preinfection Daily Oral Anticoagulation Use and All-Cause in Hospital Mortality From Novel Coronavirus 2019 at 21 Days: A Retrospective Cohort Study. (22nd January 2021) - Harrison, Raquel F.; Forte, Kenneth; Buscher, Michael G.; Chess, Adam; Patel, Amitkumar; Moylan, Tatiana; Mize, Charles Haviland; Werdmann, Michael; Ferrigno, Rockman
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Practices regarding anticoagulation use in coronavirus disease 2019 focus primarily on its efficacy in the critically ill without a clear understanding of when to begin anticoagulation. We sought to understand the association of preinfection daily oral anticoagulation use and the short-term mortality of patients hospitalized with coronavirus disease 2019. Design: Retrospective chart review. Setting: Large health system with high coronavirus disease 2019 prevalence. Patients: Patients 60 years or older admitted to the hospital with positive coronavirus disease 2019 polymerase chain reaction test. Interventions: We compared both those on warfarin and those on a direct oral anticoagulant prior to admission and throughout disease course with those who were never exposed to an oral anticoagulant. Results: Our primary outcome was inhospital mortality at 21 days from the first coronavirus disease 2019 test ordered. Patients in the direct oral anticoagulant group ( n = 104) were found to have significantly lower 21-day all-cause in hospital mortality than patients in the control group ( n = 894) both prior to adjustment (14.4% vs 23.8%; odds ratio, 0.57 [0.29–0.92]; p = 0.03) and after controlling for age, gender, and comorbidities (odds ratio, 0.44 [0.20–0.90]; p = 0.033). Patients on warfarin ( n = 28) were found to have an elevated unadjusted mortality rate of 32% versus 23.8% in the control group (odds ratio, 1.51 [0.64–3.31]; p = 0.31). After adjustment, a reduction in mortality was observed but not found to be statistically significant (odds ratio, 0.29 [0.02–1.62]; p = 0.24). There was no statistical difference noted in the number of bleeding events in each group. Conclusions: In this retrospective cohort study evaluating oral anticoagulant use among patients with coronavirus disease 2019, we found that patients who are on daily oral anticoagulation at the time of infection and throughout their disease course had significantly lower risk of all-cause mortality at 21 days. Validation of these findings should be performed on population-based levels. While research regarding anticoagulation algorithms is ongoing, we believe these results support future randomized control trials to understand the efficacy and risk of the use of early oral anticoagulation.